1995
DOI: 10.1523/jneurosci.15-05-04077.1995
|View full text |Cite
|
Sign up to set email alerts
|

Expression of m1-m4 muscarinic acetylcholine receptor proteins in rat hippocampus and regulation by cholinergic innervation

Abstract: A family of muscarinic ACh receptor genes are expressed in hippocampus, but little is known about the localization of the encoded proteins and their regulation by cholinergic innervation. Subtype-specific antibodies were used to localize m1-m4 proteins in the hippocampal formation by immunocytochemistry and to determine the alterations in the subtypes following deafferentation. Each of the receptors is differentially localized in Ammon's horn and dentate gyrus, with highly complementary distributions. m1 is wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

28
286
4
6

Year Published

1996
1996
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 382 publications
(324 citation statements)
references
References 74 publications
28
286
4
6
Order By: Relevance
“…We have previously reported that the compound shows K i values in the low nanomolar range for muscarinic receptors subtypes (18-114 nM), with a profile by ascending order of potency: M 1 4M 3 4M 4 4M 2 (Espallergues et al, 2007). All subtypes of muscarinic receptors are expressed in the hippocampus and cortex (Levey et al, 1995) and postsynaptic M 1 and autoreceptor M 2 subtypes have been shown to be crucially involved in learning and memory processes (Ghelardini et al, 1999; but see also Quirion et al, 1995;Miyakawa et al, 2001;Seeger et al, 2004). Nonselective muscarinic antagonists, such as scopolamine and atropine, impair performance in various learning and memory tasks in rodents, including eight-arm radial maze learning (Eckerman et al, 1980), contextual fear conditioning (Anagnostaras et al, 1995), water-maze learning (Sutherland et al, 1982), or passive avoidance (Espallergues et al, 2007).…”
Section: Discussionmentioning
confidence: 97%
“…We have previously reported that the compound shows K i values in the low nanomolar range for muscarinic receptors subtypes (18-114 nM), with a profile by ascending order of potency: M 1 4M 3 4M 4 4M 2 (Espallergues et al, 2007). All subtypes of muscarinic receptors are expressed in the hippocampus and cortex (Levey et al, 1995) and postsynaptic M 1 and autoreceptor M 2 subtypes have been shown to be crucially involved in learning and memory processes (Ghelardini et al, 1999; but see also Quirion et al, 1995;Miyakawa et al, 2001;Seeger et al, 2004). Nonselective muscarinic antagonists, such as scopolamine and atropine, impair performance in various learning and memory tasks in rodents, including eight-arm radial maze learning (Eckerman et al, 1980), contextual fear conditioning (Anagnostaras et al, 1995), water-maze learning (Sutherland et al, 1982), or passive avoidance (Espallergues et al, 2007).…”
Section: Discussionmentioning
confidence: 97%
“…The target for the enhanced cognition in response to this treatment was thought to be M 1 -muscarinic receptor signaling. This notion is based on the fact that the M 1 -muscarinic receptor is the most highly expressed muscarinic receptor subtype in the cortex and hippocampus (12) and that pharmacological studies point to this receptor subtype as being the primary effector of cholinergic-mediated cognition (6,24,25). However, recent studies using M 1 -muscarinic receptor knockout mice (1) together with studies using more selective pharmacological tools (9,10) have suggested that the M 1 -muscarinic receptor does not mediate hippocampal cognition directly.…”
Section: Discussionmentioning
confidence: 99%
“…In light of this uncertainty, we investigate here the possibility that the M 3 -muscarinic receptor, which is expressed widely in the central nervous system including the hippocampus (12), might play a role in Pavlovian fear conditioning learning and memory. We also probe the contribution that receptor phosphorylation might play by using a knockin mouse strain that expresses a phosphorylation-deficient mutant of the M 3 -muscarinic receptor.…”
mentioning
confidence: 99%
“…O-LM interneurons receive an important cholinergic innervation from the medial septum-diagonal band complex of the basal forebrain (Frotscher and Léránth, 1985) and are endowed with a variety of muscarinic acetylcholine receptors and nicotinic acetylcholine receptors (nAChRs) (Levey et al, 1995;Tribollet et al, 2004) that regulate their activity (Lawrence et al, 2006;Griguoli et al, 2009). An in vivo study has demonstrated a key role of cholinergic activity in amplifying theta oscillations (Lee et al, 1994), and a recent in vitro work has outlined the role of muscarinic receptors in enhancing spike reliability and precision to theta frequency input (Lawrence et al, 2006).…”
Section: Introductionmentioning
confidence: 99%